(untitled) (ARTEKS : Jurnal Teknik Arsitektur, 2023)
The traditional village of Gurusina is located in the Jerebu’u District, Ngada Regency, Flores, and is inhabited by three major tribes, namely Ago Ka’e, Ago Azi, and Kabe. The traditional houses in the Gurusina village are rich in traditional symbols originating from the traditions of its resident tribes. A fire incident that occurred in August 2018 resulted in the destruction of several traditional houses and the disappearance of symbols that had been preserved for generations. The purpose of this article is to find inspiration from the traditional symbols on the traditional houses in Gurusina village. The research method used is Ethnographic Research, where the researcher approaches the subject qualitatively to discover inspiration or foundations for the emergence of the form, function, and meaning of these symbols. The findings reveal that the symbols on the traditional houses in Gurusina village are inspired by flora, fauna, human and local beliefs. This means that the surrounding nature, human and local beliefs are the primary inspiration for the function, form, and meaning of the traditional symbols in the Gurusina village. This research theme is interesting for further investigation to understand and preserve traditional symbols in Indonesia.